Psychiatrists' attitude towards the use of clozapine in the treatment of refractory schizophrenia: A nationwide survey. (May 2019) - Daod, Essam; Krivoy, Amir; Shoval, Gal; Zubedat, Salman; Lally, John; Vadas, Limor; Weizman, Abraham; Reshef, Alon; Bloch, Boaz
Highlights: Attitudes of Israeli psychiatrists ( n  = 295) towards clozapine treatment were investigated. Although familiarity with guidelines was high, reported prescription rate of clozapine was relatively low. Allocated resources for clozapine treatment were not associated with higher prescription rate. Main barriers to prescription was fear of side effects, especially agranulocytosis, and concerns about compliance with blood tests. Abstract: Objectives: Clozapine is the most effective treatment for refractory schizophrenia, yet it remains underused in clinical practice. The current study examined the awareness, familiarity and attitude of a nationwide sample of Israeli psychiatrists regarding the use of clozapine. Methods: Data were collected using questionnaires, completed by 295 psychiatrists. Participants were asked to score questions regarding clozapine procedures; familiarity with guidelines, drug properties, prescription and attitude towards specialized clozapine resources. Results: About half (53.3%) of the psychiatrists reported initiating treatment with clozapine according to the guidelines, whereas 33% reported that they administered clozapine only after three or more unsuccessful antipsychotic treatments. Surprisingly, availability of specialized resources for clozapine treatment (such as clozapine clinics) was associated with delayed initiation of clozapine treatment, and a lower rate of clozapine administration. Barriers to clozapine use included concerns about patient adherence, side effects and partial compliance with the required blood monitoring. Conclusions: Delaying or avoiding clozapine treatment to potentially eligible patients, despite familiarity with the drug efficacy and treatment guidelines, is a major mental health concern. However, executive allocation of resources to support the use of clozapine may be ineffective in promoting clozapine use.